ANALISIS PENGELOLAN RISIKO RANTAI PASOK TEH PTPN VIII KEBUN RANCABALI UNIT SINUMBRA (Studi Kasus: PTPN VIII Kebun Rancabali Unit Sinumbra, Kecamatan Rancabali, Kabupaten Bandung, Jawa Barat) - Prabawari, Maria Vincentia Sista; Perdana, Tomy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Tea is one of the plantation commodities in Indonesia which has a production ranking in the top 10 in the world according to FAO data (2022). However, according to data from the Central Statistics Agency, tea exports in Indonesia have decreased in the last 10 years. PTPN VIII which produces tea has a broad global market, which has the 10 largest export destination countries. The decline in exports may show the need for good supply chain management with product standards and quality that can compete with other countries' products then, an effectively managed supply chain is needed. Difficulties that arise in agricultural supply chains such as perishability, seasonality, varying quality, and requiring a lot of space. This study focuses on supply chain risk at PTPN VIII Kebun Rancabali Sinumbra Unit as one of the units which position of the Sinumbra Unit in PTPN VIII Region III shows 9% and is in the eighth order of the nine existing plantations in Region III. The use of a fishbone diagram as a mapping for the risks obtained, then followed by the FMEA method to determine risk priorities and the AHP method as a tool for determining priorities in making decisions on mitigation actions. The results of this research are 18 risks in supply chain risk mapping using a fishbone diagram, then four supply chain variables are found, namely, plan, source, make, and delivery with a total of 10 risks that are the priority. Risks that are prioritized based on calculations using the FMEA method come from the plan variable, namely the work target for the production of raw materials is not implemented. All of these priority risks are then included in the AHP method for decision-making in alternative mitigation strategies, indicating the variable plan with the risk of processing work targets not being implemented is a priority in taking mitigation actions including periodic machine maintenance, increasing supervision of workers, and evaluation every six months for RKAPP.